A single-center case-control study of the association between dorsal striatal damage and nicotine addiction - Chuya Jing; Chuya Jing; Chuya Jing; Chuya Jing; Chuya Jing; Xingkai An; Xingkai An; Xingkai An; Xingkai An; Xingkai An; Xingkai An; Xingkai An; et al. (Frontiers in Neurology)
BackgroundSmoking is closely linked to pulmonary diseases, cardiovascular diseases, cancer, and other health issues, posing a significant threat to human health. The essence of smoking addiction lies in nicotine dependence, though the underlying mechanisms remain unclear. Previous studies have suggested that nicotine addiction is associated with regions such as the insula, globus pallidus, amygdala, and ventral striatum. However, our prior retrospective study indicates that the dorsal striatum may also play a role in nicotine addiction.ObjectiveOur research aims to evaluate the alterations in nicotine addiction among patients with dorsal striatum lesions at 1 month, 3 months, 6 months, and 12 months post-injury.MethodsWe collected data from patients of the First Affiliated Hospital of Xiamen University between August 2021 and August 2024. We screened some patients with dorsal striatum injury and asked a series of questions at the time points of 1 month, 3 months, 6 months, and 12 months after brain injury. Ultimately, 13 patients with dorsal lesions who met the inclusion criteria and a control group of 13 patients with brain injuries in other regions were selected.ResultsWe observed that patients with dorsal striatum damage experienced smoking cessation more readily and earlier compared to the control group. Furthermore, those with more severe dorsal striatum damage might maintain this cessation for longer. Additionally, nicotine dependence scores on the Fagerström Test for Nicotine Dependence (FTND) were lower in patients with dorsal striatum damage compared to the control group, indicating a reduced level of nicotine dependence.ConclusionThis conclusion suggests that the dorsal striatum may be associated with nicotine addiction.